Transaction-Based Recruitment in East Cirebon Industrial Area: A Thematic Analysis of Factors Driving Illicit Fee Practices in Labor Hiring - Niken Vintang Erdwiyana; Rajabani Bramantio (West Science Social and Humanities Studies, 2026)
The industrial development of East Cirebon has generated significant employment opportunities, yet has also given rise to a persistent informal phenomenon: illicit payments — known colloquially as suap or bribery — made to individuals claiming affiliation with company HR departments in order to secure employment. This study investigates the factors driving transaction-based recruitment practices in the East Cirebon industrial area, despite formal recruitment mechanisms regulated by both companies and the Regional Manpower Office (Disnaker). Employing a qualitative approach with thematic analysis (Braun & Clarke, 2006), four informants participated: one HR leader (HR-01) and three production workers (TK-01, TK-02, TK-03). Analysis generated four core themes: (1) dualism of formal-informal recruitment mechanisms; (2) structural drivers of transactional practices; (3) power relations among key actors; and (4) ethical perception and resistance to normalization. Key findings indicate that these practices are not caused by the absence of regulation, but by structural loopholes in their implementation, exacerbated by a severe labor supply-demand imbalance (ratio 1:10), economic pressures on both sides of the transaction, and community-level social norms. Policy recommendations are offered for companies, the Manpower Office, and future researchers.